α,β-Unsaturated δ-Valerolactones through RCM–Isomerization Sequence - Schmidt, Bernd; Kunz, Oliver (Synlett, 2012)
α,β-Unsaturated δ-lactones are accessible via a sequential ring-closing metathesis (RCM) double-bond migration reaction starting from butenoates of allyl alcohols. This approach proceeds efficiently with lower catalyst loadings and higher initial substrate concentrations compared to the alternative RCM of acrylates derived from homoallylic alcohols.
Keywords: ruthenium; lactones; tandem reactions; metathesis; esters